The Relationship Between Adolescents’ Knowledge About Bullying And Bullying Behavior Among Students At Mts Sabila In Hamparan Perak Village - Safra Satilla Rambe,; Wardiyah Daulay, (Indonesian Journal of Medical Anthropology, 2024)
Bullying teenagers seems very common, so that this case should be seriously handled by various parties. It is considered as a phenomenon attached to a certain group of people and is influenced by wider social context. The objective of the research is to find out the correlation of teenagers’ knowledge of bullying with bullying behavior in the student of MTs Sabila at Hamparan Perak Village. The research uses descriptive correlation method with cross sectional design. The samples are 56 teenagers, taken by using total sampling technique. The research instrument was questionnaire, and the data are analyzed by using Spearman Rank test. The result of the research show that 37 respondents (66.1%) have bad knowledge, 47 respondents (83.9%) have bad behavior p-value = 0.000 and r= -0.451 wich indicate that there is the significant correlation between teenagers’ knowledge of bullying and bullying behavior in the students of MTs Sabila at Hamparan Perak village. It is recommended that the school management, especially the counseling teachers give special attention to teenagers’ behavior at the school and provide the subject of bullying and its impact in order to change or prevent bullying behavior,